Luminescence of gallium-containing complex oxide crystal - Shevchuk, V.N. (Functional Materials, 2005)
Luminescence spectra of garnet Nd₃Ga₅О₁₂ and of acentric Ca-gallogermanate
Сa₃Ga₂Ge₄О₁₄:Nd³⁺ crystals under pulsed X-ray excitation (-1.5 ns) in 200-500 nm range
are considered. The luminescence measurements carried out at 80 К and 295 К. Time
characteristics of fast (-1 ns) emission components of the crystals are evaluated. The narrow luminescence bands (slow components) are ascribed to transitions from the ²F2₅/₂ level of Nd³⁺ ion. Рассматриваются спектры люминесценции кристаллов граната Nd₃Ga₅О₁₂ и ацентрического Сa-галлогерманата Сa₃Ga₂Ge₄О₁₄:Nd³⁺ при возбуждении короткими импульсами (-1.5 ns) рентгеновского излучения в области 200-500 нм. Измерения проведены при 80 К и 295 К соответственно. Оценены временные характеристики быстрых (-1 нс) компонент излучения кристаллов. Узкие полосы люминесценции (медленные компоненты) приписываются переходам с уровня ²F2₅/₂ иона Nd³⁺. Розглядаються спектри люмiнесценцii кристалiв гранату Nd₃Ga₅О₁₂ та ацентричного Сa-галогерманату Сa₃Ga₂Ge₄О₁₄:Nd³⁺ при збудженнi короткими iмпульсами (-1.5 ns) рентгенiвського випромiнювання в областi 200-500 нм. Вимiрювання проведено при
80 К та 295 К вiдповiдно. Оцiнено часовi характеристики швидких (-1 нс) компонент випромiнювання кристалiв. Вузькi смуги люмiнесценцii (повiльнi компоненти) приписуються переходам з рiвня ²F2₅/₂ iона Nd³⁺.